Factors affecting Kleptoparasitism by gulls in a multi-species seabird colony - García, Germán (2010)
Kleptoparasitism is defined as the stealing by one animal of food that has been caught by another. It is a well-known foraging tactic used opportunistically by many seabirds. Our study describes qualitatively and quantitatively kleptoparasitism of gulls on terns and compares the effect of prey quality (prey type and size) and environmental conditions (tide, wind direction and intensity) triggering such behavior. The rate of kleptoparasitism by Kelp Gulls (Larus dominicanus) was higher on Royal (Thalasseus maximus) than on Cayenne Terns (T. sandvicensis eurygnatha). However, the percentage of successful attacks on both species was similar (∼42%). We used an information-theoretic approach to determine the relative importance of prey quality and environmental conditions in triggering kleptoparasitism. We found that more valuable prey triggered kleptoparasitism whereas the environmental conditions included in the models didn't affect the rate of such behavior significantly. Our study shows the importance of prey quality in triggering kleptoparasitism and how this behavior can remove an important portion of food brought to the tern colony.